JEWISH ISSUE IN FRIEDRICH GORENSTEIN’S WRITING - Vasiljeva, Elina (European Scientific Journal, ESJ, 2013)
The paper discusses the specific features in the depiction of the Jewish issue in the writings by Friedrich Gorenstein.The nationality of Gorenstein is not hard to define, while his writing is much more ambiguous to classify in any national tradition. The Jewish theme is undoubtedly the leading one in his writing. Jewish issue is a part of discussions about private fates, the history of Russia, the Biblical sense of the existence of the whole humankind. Jewish subject matter as such appears in all of his works and these are different parts of a single system. Certainly, Jewish issues partially differ in various literary works by Gorenstein but implicitly they are present in all texts and it is not his own intentional wish to emphasize the Jewish issue: Jewish world is a part of the universe, it is not just the tragic fate of a people but a test of humankind for humanism, for the possibility to become worthy of the supreme redemption. The Jewish world of Gorenstein is a mosaic world in essence. The sign of exile and dispersal is never lifted.